(untitled) (Research, Society and Development, 2023)
Introduction: Idiopathic intracranial hypertension (IIH) is a syndrome characterized by signs and symptoms of elevated intracranial pressure without the identification of tumor or ventriculomegaly. The aim of this study is to evaluate the epidemiological profile of children diagnosed with IIH in southern Brazil. Methods: This is a retrospective study, through the analysis of medical records and complementary exams. The medical records of patients diagnosed with IIH from January 2012 to September 2022 were evaluated. Results: Data from 33 children were analyzed and the mean age at diagnosis was 9 years, 66.7% of whom were female. In patients less than 8 years of age, the mean weight Z-score was -0.32 (SD :1.88). Of the analyzed patients, 66.7% had symptoms for up to one month, 93.3% had primary IIH and 86.7% had headache as the first symptom. Regarding treatment, 90.0% responded to monotherapy and 13.3% required surgical intervention. There was a higher risk of surgery in patients who had higher cerebrospinal fluid opening pressure at diagnosis (p=0.029). Visual sequelae at hospital discharge were observed in 47.1% of patients. Conclusion: Clinical signs and symptoms can be variable in pediatrics, requiring additional tests. A higher prevalence of IIH was observed in female adolescents. There is an increase in incidence over time, which reinforces the care and attention for this condition in pediatrics.